2022
DOI: 10.1186/s12888-022-04146-0
|View full text |Cite
|
Sign up to set email alerts
|

Information needs and sources of information among people with depression and anxiety: a scoping review

Abstract: Background Previous studies have identified substantial unmet information needs in people with depression and anxiety. Sufficient information about the disorder, treatment, available services, and strategies for self-management is essential as it may influence quality of care and patients’ quality of life. This scoping review aimed to provide a broad overview of information needs of people with depression and anxiety as well as the sources that they use to seek this information. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Online information‐seeking behaviour is also common in individuals suffering from mental and anxiety disorders (Chan et al, 2022). The dominant information needs of such individuals include additional information about their general condition and more specific details about potential treatments or coping mechanisms (Chan et al, 2022; Liebherz et al, 2015). It seems plausible that similar behaviours and needs may be observed in individuals suffering from various forms of biophobia as part of their coping strategy.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Online information‐seeking behaviour is also common in individuals suffering from mental and anxiety disorders (Chan et al, 2022). The dominant information needs of such individuals include additional information about their general condition and more specific details about potential treatments or coping mechanisms (Chan et al, 2022; Liebherz et al, 2015). It seems plausible that similar behaviours and needs may be observed in individuals suffering from various forms of biophobia as part of their coping strategy.…”
Section: Methodsmentioning
confidence: 99%
“…Online information-seeking behaviour is also common in individuals suffering from mental and anxiety disorders (Chan et al, 2022).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Its main symptoms include loss of interest and appetite, anxiety and melancholy, frustration, helplessness, weakness and feelings of guilt or shame [3,4]. The World Health Organization (WHO) has reported that 25% of individuals worldwide could experience a mental disease at some time in their lives, highlighting that depression constitutes a major contributing cause to the global rise in women's disability-adjusted life years [1,2,5]. Pregnant women undergo physiological, hormonal, and psychological changes, which could enhance the likelihood of mental health disorders [6].…”
Section: Introductionmentioning
confidence: 99%
“…Depression and anxiety are common mental disorders and leading causes of disability worldwide (Li et al., 2022). Based on 2021 data (Abeysekera & De Zoysa, 2021 ; Chan et al., 2022 ), the worldwide prevalence of depression and anxiety per 100,000 persons was found to be 3153 and 4802 cases, respectively. Of these, 15–20% of children and adolescents also suffered from anxiety and depression.…”
Section: Introductionmentioning
confidence: 99%
“…Of these, 15–20% of children and adolescents also suffered from anxiety and depression. The recent COVID‐19 pandemic had also significantly increased the prevalence of depression and anxiety disorders (Chan et al., 2022 ). The typical symptoms of depression include low mood, decreased interest, memory loss, slow thinking, decreased volitional activity, sleep disturbances, loss of appetite, and suicidal thoughts.…”
Section: Introductionmentioning
confidence: 99%